1970
DOI: 10.3329/bjsir.v45i3.6533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Spirulina platensis</i> on Lipid Profile of Long Evans Rats

Abstract: To study the Effect of Spirulina platensis on lipid profile of Long Evan rats, an experiment was conducted by feeding the rats with diets supplemented with Spirulina platensis dry powder. Five different types of diets were included in the feeding. Group A containing high fat and high sugar considered as control-01. Group B with high fat, high sugar and 0.5% Spirulina. Group C with high fat, high sugar and 2.5% Spirulina. These three groups were included in Diet-1. Group D with laboratory diets considered as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…25 In Long Evans rats fed a high-fat and high-sugar diet, supplementation of 0.5% or 2.5% SP for 4 weeks increased serum TG, while serum TC was significantly reduced by SP. 26 It was demonstrated that SP supplementation significantly increased serum TC in ovariectomized female Wistar rats fed 0.08 g/kg BW of SP per day for 6 weeks, but serum TG was decreased with SP supplementation at 0.8 g/kg BW. 27 When broiler chickens were fed a diet supplemented with 1% SP for 1 month, serum TC levels were decreased.…”
Section: Discussionmentioning
confidence: 96%
“…25 In Long Evans rats fed a high-fat and high-sugar diet, supplementation of 0.5% or 2.5% SP for 4 weeks increased serum TG, while serum TC was significantly reduced by SP. 26 It was demonstrated that SP supplementation significantly increased serum TC in ovariectomized female Wistar rats fed 0.08 g/kg BW of SP per day for 6 weeks, but serum TG was decreased with SP supplementation at 0.8 g/kg BW. 27 When broiler chickens were fed a diet supplemented with 1% SP for 1 month, serum TC levels were decreased.…”
Section: Discussionmentioning
confidence: 96%
“…Thirty male albino rats of Sprague Dawely strain weighing an average of (170 ±10 g) were used in the study and obtained from Vaccine and Immunity Organization, Helwan Farm, Cairo, Egypt. After the adaptation period of seven days, the animals were divided into five equal groups (6 rats each) as follows: The chosen dose of MSG was built on the harmfulness levels described by previous studies Hassan, et al, (2020), and the doses of Spirulina were selected from published literature according to Mridha et al, (2010).…”
Section: Experimental Designmentioning
confidence: 99%
“…Table 1 includes all of the items used in the first and second stages of the experiment and control diet preparations. The diet was created using a conventional procedure, and the components were bought at a nearby market [ 28 ]. Therefore, proximate composition of control diet, HFD, and oil-based formulated diet are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%